Answer:
Certainly! Let’s compare the two functions, f and g, on the interval ([0,4]).
Function f:
It is an exponential function with an initial value of 64.
It decreases by 50% as x increases by 1 unit.
The general form of f(x) is: (f(x) = 64 \cdot (0.5)^x).
Function g:
It is represented by the given table:
X g(x)
0 75
1 43
2 27
3 19
4 15
We can observe that g(x) is decreasing as x increases.
Now let’s compare the average rates of decrease for both functions:
Function f:
Initial value: (f(0) = 64)
Final value at (x = 4): (f(4) = 64 \cdot (0.5)^4 = 4)
Average rate of decrease: (\frac{{f(0) - f(4)}}{4} = \frac{{64 - 4}}{4} = 15)
Function g:
Initial value: (g(0) = 75)
Final value at (x = 4): (g(4) = 15)
Average rate of decrease: (\frac{{g(0) - g(4)}}{4} = \frac{{75 - 15}}{4} = 15)
Since both functions have the same average rate of decrease on the interval ([0,4]), the correct statement is:
C. Both functions are decreasing at the same average rate on that interval.
If you have any more questions or need further clarification, feel free to ask!
Step-by-step explanation: